Tingkat Kesejahteraan Rumah Tangga Anggota Kelompok Wanita Tani Lahan Kering di Yogyakarta - Ayu Putri Merry Anisya (Journal of Agribusiness Science and Rural Development, 2024)
The level of farmer welfare is an important and complex topic in the agricultural and economic context. Farmer welfare not only includes financial aspects, but also social, health and environmental factors that influence daily life. This research aims to determine the level of welfare of households belonging to the women's farmer group in Pakel Jaluk Village by utilizing dry land. The basic method in this research is descriptive analytical with a sample collection method of 38 respondents. According to the GSR criteria, households belonging to the women's farmer group in Piyaman Village are classified as more prosperous with a GSR value of 0.84 (< 1). So it is better for commodities cultivated in home gardens to be replaced or supplemented with commodities that are of high value but do not require a lot of work time, such as bananas and jackfruit. Bananas have been cultivated but their numbers are still quite low. Each household records all forms of household income and expenditure so that it is better maintained or the PKK can provide training regarding household financial management.